Economies of Scale in the Malaysian Insurance Industry - Zakaria, Noor' Aziah (1993)
The insurance industry in Malaysia contributes only a small percentage to the Gross National Product (GNP). Hence in the past not much attention was paid to this industry. The recession years of the mid eighties have, however, forced the authorities to look at the industry rather closely. In fact, the government has made further intervention into the industry by placing it under the supervision of Bank Negara Malaysia (BNM). Since the takeover, the BNM has been active in revising the present insurance Act and has been issuing a number of guidelines to assist insurance companies to operate in an efficient manner. From the statistics reported in, the Annual Report of the Director General of Insurance (DGI), there has been some improvements in both sectors. For example, the forfeiture and surrender rates for the life sector has decreased due to improvement in the insurers' services. In the general sector on the other hand, the commission and management expense rates for the high premium bracket insurers (> RM 45 million) were able to be reduced even though for the low premium bracket insurers « RM 20 million) it was still high. The thesis analysed the operation of the insurance industry by examining their cost of operation. This is done by estimating the industry's cost function as well as estimating the minimum efficient scale (MES). The estimation of the cost function made use of the statistical cost function approach. In the analysis of the life sector, the lapse ratio, new policies and the dummy variable for ownership (foreign or local) have been shown to affect the average cost. The life sector also experienced economies of scale but the number of companies which were able to reach that MES level was still small compared to insurers which experienced economies of scale but failed to have the minimum scale of cost. Estimation results for the general insurance industry showed that the industry did experience the economies of scale. However, the level of the minimum efficient scale was not able to be determined. Results showed that in general foreign companies were doing better than the locals. The overall results for both sectors implied that the size of the local companies beside the internal problems faced by the sector e.g. high costs for the general, was a constraint for achieving the efficient scale of production. The B NM should continue supervising and regulating the industry so that the companies in the industry can perform to expectations.